Research (AR) Container Port Selection in Contestable Hinterlands - Kemal AKBAYIRLI (Journal of ETA Maritime Science, 2016)
Port competition has become fiercer with each passing day due to the developments in hinterland networks, port innovations at ports, port privatization policies and the changing specific service expectations of port users. This competitive environment has led to shifting the hinterland areas from captivity to contestability. The customer focus in determining the level of service quality and service diversity is crucial to gain a share from such contestable and competitive hinterlands. Therefore, the main aim of this study is to determine port selection criteria of port users and to develop a model for measuring selection criteria of port users in contestable hinterlands. A confirmatory factor analysis was applied to develop a model for port selection in a contestable hinterland. The model includes 7 main constructs and total 32 criteria. The model reveals that competitiveness of ports in contestable hinterlands is not only affected by ports’ own services but external ones such as number and frequency of shipping lines calling at the port are also vital.